Electron spin coherence and electron nuclear double resonance of Bi donors in natural Si. - George, R; Witzel, W; Riemann, H; Abrosimov, N; Nötzel, N; Thewalt, M; Morton, J (2010)
Donors in silicon hold considerable promise for emerging quantum technologies, due to their uniquely long electron spin coherence times. Bismuth donors in silicon differ from more widely studied group V donors, such as phosphorous, in several significant respects: They have the strongest binding energy (70.98 meV), a large nuclear spin (I=9/2), and a strong hyperfine coupling constant (A=1475.4  MHz). These larger energy scales allow us to perform a detailed test of theoretical models describing the spectral diffusion mechanism that is known to govern the electron spin decoherence of P donors in natural silicon. We report the electron-nuclear double resonance spectra of the Bi donor, across the range 200 MHz to 1.4 GHz, and confirm that coherence transfer is possible between electron and nuclear spin degrees of freedom at these higher frequencies.